2016
DOI: 10.22256/pubvet.v10n2.138-146
|View full text |Cite
|
Sign up to set email alerts
|

Leptospirose – Revisão

Abstract: . Tel/Fax: +55 11 30917690 RESUMO. A Leptospirose é uma doença infecciosa de caráter sistêmico, sua ocorrência é evidenciada em regiões de clima tropical e subtropical, sendo prevalente nas Américas, onde ocorre de forma endêmica na América Latina e Caribe. No Brasil, a doença tem caráter endêmico, sendo comuns surtos epidêmicos na época das chuvas. A Leptospirose também é considerada uma doença de risco ocupacional, atingindo trabalhadores agrícolas (arrozais e canaviais), mineradores, coletores de lixo e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
20

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 7 publications
0
7
0
20
Order By: Relevance
“…Additionally, these animals may be chronically infected. Approximately ten days after initial infection, opsonizing antibodies appeared in the bloodstream; these antibodies promote the gradual elimination of leptospires from the bloodstream, then migrate to immune-protected sites, such as the kidney and genital tract, potentially remaining there for prolonged periods (SIMÕES et al, 2016) and considerably reducing the number of antibodies that can be identified by MAT. The antibody titer levels detected by MAT depend primarily the level of exposure of a given population to the agent.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, these animals may be chronically infected. Approximately ten days after initial infection, opsonizing antibodies appeared in the bloodstream; these antibodies promote the gradual elimination of leptospires from the bloodstream, then migrate to immune-protected sites, such as the kidney and genital tract, potentially remaining there for prolonged periods (SIMÕES et al, 2016) and considerably reducing the number of antibodies that can be identified by MAT. The antibody titer levels detected by MAT depend primarily the level of exposure of a given population to the agent.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, to inform health prevention efforts and educational measures, it is important that researchers assess the prevalence of the infection in herds from refrigerated slaughterhouses. In this way, any possible occupational infections can be avoided (GONÇALVES et al, 2006;SIMÕES et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Leptospirosis is an infectious disease that is considered occupational, since exposure to infected animals during work can infect slaughterhouse and rural workers, veterinarians, among others (GONÇALVES et al, 2006(GONÇALVES et al, , 2013SIMÕES et al, 2016). In the context of occupational disease, workers often lack knowledge about leptospirosis, resulting in failure to use, or misuse of, personal protective equipment (PPE).…”
Section: Introductionmentioning
confidence: 99%
“…A leptospirose é causada por bactérias do gênero Leptospira, que acomete humanos e animais, os quais participam da cadeia epidemiológica como doentes, portadores assintomáticos e reservatórios (FIGUEIREDO et al, 2001). A organização estrutural e a composição química das leptospiras são semelhantes às de bactérias Gram-negativas, como a membrana externa que envolve toda a célula, os filamentos axiais denominados de flagelos periplasmáticos e os cilindros protoplasmáticos, que incluem a membrana celular e a capa de peptidioglicano da parede celular (SIMÕES et al, 2016).…”
Section: A Bactériaunclassified
“…Nas cidades brasileiras, sua ocorrência está relacionada a condições inadequadas de habitação, permitindo o contato dos humanos com águas ou solos contaminados, principalmente em períodos de chuvas e enchentes, favorecendo a infecção (FONTES et al, 2010). A leptospirose foi descrita pela primeira vez em 1880, no Cairo, por Larrey, no entanto, foi em 1886 que Weil descreveu minuciosamente quatro casos clínicos em humanos (SIMÕES et al, 2016). No Brasil, os primeiros relatos sobre leptospirose foram publicados no Rio de Janeiro, em 1917, por Aragão, sobre "A presença do Spirochaeta icterohaemorrhagiae nos ratos do Rio de Janeiro" (OLIVEIRA, 2008).…”
Section: A Introduçãounclassified